CHARACTERISTICS OF PHYSICAL PROPERTIES OF SOIL UNDER COCOA PLANTS IN THE LOWLANDS OF LAPE VILLAGE AND THE NAPU HIGHLANDS - Ita Mowidu; Andri Amaliel Managanta; Ria Dewiyanti Tologana; Fitria (Agropet, 2026)
Cocoa is a plantation commodity of high economic value. Soil physical properties are one of the factors supporting production. Elevation is believed to influence the physical properties of the soil. The study aims to determine the physical soil characteristics of lowland and highland cocoa plantations in Poso Regency. The research was conducted from November 2024 to January 2025. The treatment of landscape conditions—specifically flat terrain and slopes in both lowlands and highlands—was implemented using a Randomized Complete Block Design (RCBD). Each treatment was replicated 10 times. The soil physical properties observed were soil color, bulk density (BV), porosity, available water content, and drainage pores. Research results indicate that the soil beneath the cocoa canopy in the Napu highlands is dark in color, whereas in the Lape lowlands, it is light-colored. This is attributed to differences in parent material and climatic conditions. In the Lape lowlands, on the sloping landform, the soil has a bulk density of 0.78 g/cm³, a porosity of 71.08%, an available water content of 38.94% by weight (or 30.37% by volume), and drainage pores of 6.75%. In the valley landform, the soil bulk density is 1.14 g/cm³, porosity is 57.40%, available water content is 39.47% by weight or 45.15% by volume, and drainage porosity is 7.52%. In the sloping terrain of the Napu Highlands, the soil has a bulk density of 1.05 g/cm³, a porosity of 60.49%, an available water content of 38.17% by weight (or 39.92% by volume), and a drainage porosity of 11.48%. In the valley landform, the bulk density is 0.69 g/cm³, porosity is 75.36%, available water content is 39.75% by weight or 27.35% by volume, and drainage pores account for 12.39%. The level of available water at all locations is classified as high (>25%), and plant roots do not encounter mechanical impedance. Keywords: lowlands, highlands, cocoa, soil physical properties